A imagem no livro didático de Educação Infantil nas décadas de 1960 e 1970 - Silva, Tatiane Godoy Campos da (2020)
In the 1960s and 1970s, the growth of publications focused on Early Childhood Education was noted in the production of Brazilian textbooks. Despite the multiplicity of shapes and configurations of these books, they share a characteristic that is easy to recognize when flicking through their pages: the constant presence of images as opposed to the written text. Based on the collection of Biblioteca do Livro Didático (BDL), from Faculdade de Educação of Universidade de São Paulo (FE-USP) and reflecting upon the discourse on the image given by institutions related to Brazilian education in the period, especially in relation to uses and requirements related to the image, this research aims to present an overview of the material aspects of textbooks at Early Childhood Education segment in the 1960s and 1970s, focusing especially on its illustrations, from two aspects: the space of image in the textbook and an analysis of the illustrations presented in these books, arguing the image as a vehicle which is capable of revealing cultural, historical and social aspects of a given moment in a society